The growth of intelligence in the pre-school years [videorecording]. - Piaget, Jean,|d1896-1980.; Lavatelli, Celia Stendler 1911-. (San Luis Obispo, CA Davidson Films, 1972)
Children from infancy to six years of age perform tasks designed by Jean Piaget and his collaborators which reveal how intellectual thought develops and manifests itself in early childhood.
Videocassette version of a 1972 motion picture released by Davidson Films and Sterling Educational Films.
Narrator, Celia Stendler Lavatelli.
Keywords: Child development; Child psychology